Optimisation of tensile and compressive behaviour of PLA 3D printed parts using categorical response surface methodology. (8th August 2022) - Waseem, Muhammad; Habib, Tufail; Ghani, Usman; Abas, Muhammad; Jan, Qazi Muhammad Usman; Khan, Muhammad Alam Zaib
The present study aims to optimise process parameters of 3-D printed polylactic acid (PLA) part using response surface methodology (RSM). The input printing process parameters considered are layer height ( L ), infill percentage ( I ), raster width ( R ) and infill patterns ( P ) (i.e., linear, hexagonal and diamond), while the responses are tensile and compressive strengths. Box Behnken array design is applied for experimental runs and also to fit quadratic regression models. The results revealed that significant parameters affecting compression strength performance are I, I 2, R, and interaction of I and R, for tensile strength, are L, I, I 2, R, P, and interaction of P with L and I . The simultaneously optimised parameters obtained based on composite desirability function for compression and tensile strength are L = 0.1 mm, I = 100%, R = 0.4 mm, and P = hexagonal, while the obtained maximum compression and tensile strength are 9.06 kN and 1.67 kN.